Paul Celan a través de textos de Píndaro y de Hölderlin. Trabajar las lenguas o traducción y reescritura: Un resumen de este trabajo fue leído en el XVI Congreso de la Asociación Latinoamericana de Estudios Germanísticos (ALEG), Buenos Aires, 27 de noviembre al 1° de diciembre de 2017 y publicado en actas, con el título: «Paul Celan – Hölderlin – Píndaro: traducción e interpretación. Travesía de los textos y de los autores» (disponible en: http://eventosacademicos.filo.uba.ar/index.php/ALEG/ALEGXVI/paper/view- File/3695/2587) (El Hilo de la Fabula, 2019)
Difficulties in reading and interpreting Paul Celan’s texts in relation to history and, especially, to the Holocaust, led us to propose this work in which the dimensions of translation and interpretation (Romano Sued 2007, Steiner 1975) mesh well with Celan’s rewriting of texts by German authors who en-couraged Nazism. We propose the decipherment of the connection between a Hölderlin’s version of ‹‹Das Höchste››, a fragment of Pindar, and then Paul Celan’s rewriting of Hölderlin in his poem ‹‹Ich trink Wein aus zwei Gläsern›› (GW III, 108); which in tandem requires deep diving into the natureof the Celanian poem and the intentionality of the poet. All these arising problematizations and the conflict of such an in- tertextual approach will allow us to understand the authors’ position in relation to their texts and the world they ascribe to.
Keywords: Translation; Interpretation; History; Language